A study on spectrum of conventional risk factors in acute coronary syndrome in NGMCTH, Nepal - Pandey, Brijesh; Shrestha, Gopal Prasad; Lamichhane, Nawaraj; Pandey, Shikha; Lamichhane, Shruti (Nepal Mediciti Medical Journal, 2024)
BACKGROUND ACS is one of the medical emergencies encountered in clinical practice. Risk factors for any disease conditions are a gesture for its futuristic impact. Surprisingly the prevalence of cardiovascular diseases, especially CAD is rising in developing countries. The presence of CAD embarks physical, psychosocial and economic burden to the individuals, family, society and nation. Conventional risk factors are one of the causal risk factors for CAD. The aim of this research was to study the following risk factors in ACS: Age, Smoking, HTN, DM, Dyslipidemia, Gender and Family history of CAD. METHODS This was a Single Center Hospital Based Observational Prospective Cross-sectional Study conducted at Nepalgunj Medical College Teaching Hospital (NGMCTH). All diagnosed cases of ACS with total of 100 subjects were included from Emergency department, Medical wards, Coronary Care Unit (CCU) and OPD. Duration of study was one year from March 2016 to march 2017 after approval from IRC in April. Clinical data was obtained by questionnaire and later entered into Excell and further analysis was done with SPSS software version 20.0. All categorical variables were expressed using percentage and continuous variables as mean and standard deviations and association was calculated using Chi-square test. RESULTS Out of 100 subjects 71% were male and 29% females. The age range was between 23 to 91 years and the mean age was 69.9±12.83. This study showed 45% subjects had STEMI, 27% were having NSTEMI and 28% were suffering from Unstable angina (UA). Hypertension was found in 73%, Male gender was seen in 71%, Family History of CAD was found in 13%, Smoking was found in 69%, DM was found in 63% and 56% were having Dyslipidemia. CONCLUSION Out of total 100 subjects enrolled hypertension was the most common conventional risk factor (73%). It was statistically significant (p value=0.02). Out of total patients 73% had at least one risk factor for ACS. Male gender was the second common risk factor (71%). STEMI was the most common ACS (45%).